(3aJhM GdZjHs - (3YHO GdbGOQ Hf CHj UGdM Hf YHO Gddg GdLjdGfj, CHh eMeO,J (B561 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYdGeI CHheMeO YHOGdbGOQ GdLjdj GdPj de jUa Yf MQ GdbdH s
(3BNQgG (B:s
(3hbGd QVj Gddg Yfg cf eY Gddg YR hLd hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs